IMPLEMENTING VOCABULARY SELF-COLLECTION STRATEGY IN THE EFL COLLEGE CLASSROOM IN ENGAGING STUDENTS’ COMMUNICATIVE CLASSROOM - Elih Sutisna Yanto (Siliwangi University, 2017)
The application of vocabulary self-collection strategy (VSS) to EFL classroom has been well-published, but little is known about how this strategy is applied to tertiary grades education context. To fill this gap, this small-scale research reports the findings of the implementation of vocabulary Self-Collection-Strategy (VSS) in growing and developing tertiary students’ vocabulary in terms of second language research terminologies.Vocabulary self-collection strategy is an interactive-learning instructional strategy that promotes word consciousness, as students are actively involved in identifying important words from their reading through video to share with partners of their class so that communicative classroom is engaging. Qualitative data show that this strategy encouraged independent learning of the students in understanding research terminologies and their responses toward this strategy are positive. Students engaged in their own learning, discover how to recognize unfamiliar or interesting words from their readings, develop their vocabularies, and become word conscious. In addition, Vocabulary Self-Collection Strategy can be a catalys for engaging students in post listening tasks such as write a brief summary of the text from the video; explain to students’ partner in students’ own words that text was about